Caregiver reported seizure precipitants and measures to prevent seizures in children with Dravet syndrome. (December 2022) - Bjurulf, Björn; Reilly, Colin; Hallböök, Tove
Highlights: Seizure provoking factors reported by caregivers are common in Dravet syndrome. The most common provoking factors were infection, physical activity, and fatigue. Seizures had been provoked by reduced temperature in 20/42 (48%) children. Measures employed to avoid seizures are common, restricting family life. The most common measures were avoidance of warm weather and physical activity. Abstract: Objective: The aim of this population-based, cross-sectional study was to describe caregiver-reported seizure precipitants, measures taken to prevent seizures and rescue therapies in children with Dravet Syndrome (DS). Methods: In a population-based study, caregivers of 42/48 Swedish children with DS born between 2000 and 2018 were interviewed. Frequency of precipitants, preventive measures, and rescue therapies were compared between children born 2000-2009 and 2010-2018 and between `severe´ and `less severe´ epilepsy. Results: All children had experienced precipitants. Preventive measures were employed in all. Seizures had been provoked by a median of seven (range 2-11) out of 13 factors. A median of eight (range 1-17) preventive measures out of 19 were reported. The most common precipitants were fever (n=42, 100%), and afebrile infections (n=39/42, 93%). Afebrile infections (p=0.014) and reduced ambient temperature (p=0.006) were more common precipitants in younger children, and bright light in children with severe epilepsy (p=0.013). The most common factors avoided were warm weather (n=35/42, 83%) and physical activity (n=27/42, 64%). It was more common to avoid strong emotions (p=0.035) and reduced temperature (p=0.002) in younger children, and to avoid infections (p=0.024) and crowds (p=0.046) in children with 'severe' epilepsy. Many children (n=28/42, 67%) or their siblings (n=16/34, 47% of individuals with siblings) had stayed home to avoid infections in school/day-care. Use of emergency medicines was more frequent in younger children (p=0.006) and in children with 'severe' epilepsy (p=0.007). Significance: Caregiver-reported seizure precipitants are common in DS. Caregivers employ a range of measures to avoid seizures, restricting family life.